Assessment for Learning Practices and Their Effect on Motivation in Science Labs - Ayu Ardini; Wahyu Erwanda; Fatoni Aziz; Nur Farhana Binti Salleh (ESENSI: Jurnal Riset Pendidikan, 2026)
This study examines the effect of Assessment for Learning (AfL) practices on student motivation in science laboratory settings. Motivation remains a persistent issue, especially when assessment focuses on grades and final outputs rather than learning processes. This research addresses that gap by analyzing how formative assessment strategies influence intrinsic motivation, perceived autonomy, perceived competence, and student engagement during laboratory activities. A quasi-experimental design was used, involving an experimental group that applied AfL practices and a comparison group that used conventional assessment methods. Data were collected through motivation questionnaires, classroom observations, and student reflections administered before and after the intervention. Quantitative analysis measured changes in motivational dimensions, while qualitative data supported interpretation of engagement and learning behaviors. The findings show that AfL practices significantly enhance student motivation in laboratory contexts. Students receiving formative feedback, self-assessment, peer assessment, and structured milestone tasks reported higher intrinsic motivation and stronger perceptions of autonomy and competence. They also demonstrated increased engagement, persistence, and reflective learning behaviors. In contrast, the comparison group showed minimal change. These results confirm that assessment design directly shapes laboratory learning experiences and can foster deeper, sustained student motivation.